The role of Lobectomy in Glioblastoma management: A Retrospective series - Christina K. Arvaniti; Alexandros G. Brotis; Jacob S. Young; Sivani Sivanrupan; Gracia Menna; Masahiro Nishide; Philippe Schucht; Mitchel Berger; Kostas N. Fountas (Brain and Spine)
Introduction: Treatment choices for glioblastoma (GB) remain scarce. Multiple clinical studies have demonstrated the importance of supramaximal resection. Recently, it is emphasized the efficacy of lobectomy as treatment option in GB patients, achieving the maximum overall survival (OS) and progression free survival (PFS). Research question: The primary aim of this study is to assess the OS and PFS of GB patients undergoing lobectomy, compared to those undergoing lesionectomy. Secondary aims include the identification of potential survival modifiers among clinical parameters. Materials and methods: This retrospective analysis consists of a multicenter case series of GB patients who underwent lobectomy or lesionectomy between January 2015 and December 2022. Primary outcome included OS and PFS. Identification of potential survival modifiers and postoperative complications were also recorded. Kaplan-Meier survival curves were generated to assess overall survival. Multivariate analyses were performed to identify factors associated with survival. Results: This study included 43 patients. There were 29 cases of lobectomy and 14 cases of lesionectomy. The median OS in lobectomy group was 34 months, compared to 15 months in the lesionectomy group. Multivariate regression analysis indicated that advanced age, tumor location, neurological deficits and the performance of lesionectomy were associated with poorer survival outcomes. Discussion and conclusions: Lobectomy in GB cases is associated with increased OS, compared to lesionectomy. In our series, we demonstrated a significantly better survival with lobectomy than lesionectomy. However, there are complications associated with lobectomy. The identification of the subgroup of patients who would benefit from a lobectomy needs to be addressed.